(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This thesis analyzes the stages of development of modern Russian linguistics, its scientific and theoretical foundations, and directions of practical application. It highlights the most pressing issues in contemporary linguistics, new methodological approaches, the formation and development trends of fields such as computational linguistics, corpus linguistics, pragmalinguistics, and sociolinguistics. The paper also examines practical aspects of learning, teaching, and translating the Russian language, as well as key principles of linguodidactics.